2020
DOI: 10.21203/rs.3.rs-88943/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The molecular tweezer CLR01 improves behavioral deficits and reduces tau pathology in P301S-tau transgenic mice

Abstract: Background: Molecular tweezers (MTs) are broad-spectrum inhibitors of abnormal protein aggregation. A lead MT, called CLR01, has been demonstrated to inhibit the aggregation and toxicity of multiple amyloidogenic proteins in vitro and in vivo. Previously, we evaluated the effect of CLR01 in the 3×Tg mouse model of Alzheimer’s disease, which overexpresses mutant human presenilin 1, amyloid β-protein precursor, and tau and found that subcutaneous administration of the compound for one month led to a robust reduc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
0
9
1
Order By: Relevance
“…Therefore, these macromolecules may work as singular molecular receptors for specific targets that can be used in numerous applications in biology and medicine [114]. Among the different applications, it was reported that a lysine-binding tweezer (CLR01) inhibits the self-assembly of different human amyloidogenic proteins, including Aβ protein, tau, and α-synuclein in vitro and in vivo [115,116]. CLR01 alters the assembly process and promotes the formation of non-amyloidogenic structures that can be efficiently removed by host clearance mechanisms (Figure 2a).…”
Section: Molecular Tweezersmentioning
confidence: 99%
“…Therefore, these macromolecules may work as singular molecular receptors for specific targets that can be used in numerous applications in biology and medicine [114]. Among the different applications, it was reported that a lysine-binding tweezer (CLR01) inhibits the self-assembly of different human amyloidogenic proteins, including Aβ protein, tau, and α-synuclein in vitro and in vivo [115,116]. CLR01 alters the assembly process and promotes the formation of non-amyloidogenic structures that can be efficiently removed by host clearance mechanisms (Figure 2a).…”
Section: Molecular Tweezersmentioning
confidence: 99%
“…Tau-seeds were prepared from PS19-mouse hippocampal extracts and added to biosensor cells for measurement of intracellular tau aggregation as described previously 48 . CLR16 was added 24 h after seeding.…”
Section: Tau Seedingmentioning
confidence: 99%
“…Many host-guest pairs have been used in 3 guest-conjugated targets in complex biological media. 17,18,19,20,21,22,2324,25,26,27,28,29,30 It is even more challenging to achieve in situ capture in living animals, and there are only very limited successful examples via employing either monovalent 31,32 or multivalent 33,34 systems. In situ capture requires the host-guest pairs to be bioorthogonal, that is, the host-guest pairs are not interfered by biomolecules and salt ions.…”
Section: Introductionmentioning
confidence: 99%